2015
DOI: 10.1039/c4cc10375k
|View full text |Cite
|
Sign up to set email alerts
|

A simple access to transition metal cyclopropenylidene complexes

Abstract: We report the first example of BAC-Cu complex (BAC = bis(diisopropylamino)cyclopropenylidene) and its use as a carbene-transfer reagent, allowing access to Au-, Pd-, Ir-and Rh-BAC compounds. Catalytic experiments show the high activity of the [CuCl(BAC)] complex in Click chemistry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
34
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 62 publications
2
34
0
Order By: Relevance
“…The results are compared with those obtained with the [Cu(Cl)(SIMes)] 1 CuCl ,15a,26b,27 and the recently reported [Cu(Cl)(BAC)] 5 CuCl (Figure 3). 28 Three different substrate sets were chosen. The reactions were conducted at room temperature, without solvent, and using 0.5 mol% of catalyst loading.…”
Section: Resultsmentioning
confidence: 99%
“…The results are compared with those obtained with the [Cu(Cl)(SIMes)] 1 CuCl ,15a,26b,27 and the recently reported [Cu(Cl)(BAC)] 5 CuCl (Figure 3). 28 Three different substrate sets were chosen. The reactions were conducted at room temperature, without solvent, and using 0.5 mol% of catalyst loading.…”
Section: Resultsmentioning
confidence: 99%
“…8 A second major class of carbocyclic carbenes is represented by the cycloheptatrienylidenes (CHTs), the first examples of which were reported in 1978 by Jones et al 9 In 2006 Bertrand et al succeeded in the isolation of the first free cyclopropenylidene derivative, 10 but in contrast to the isolation of the first free NHC by Arduengo in 1991 11 this did not prompt a comparable breakthrough, although some studies suggested that carbocyclic carbene ligands have similar potential in catalysis. [12][13][14] The lag in their development also shows up in the fact that only within the last two years the first Au-CHT complex 15 and a Cu-based transmetallation agent for cyclopropenylidene ligands 16 were reported -landmarks long established in NHC chemistry. 3 Like the NHCs, CHTs and cyclopropenylidenes act mainly as s-donors with only minor backbonding and all three classes generally feature similar M-C carbene bond lengths.…”
mentioning
confidence: 99%
“…The chemical shift of the carbocyclic carbene-C appears considerably more downfield than that of the NHC: 185. 16 (in the solid state). However, this is still a tremendous upfield-shift compared to literature-known Pd complexes of isolated CHT-ligands, for which carbene resonances have been reported in a region of ca.…”
mentioning
confidence: 99%
“…26,27 Note that all these gold, silver and copper complexes can be prepared by simple addition at room temperature of the free carbene 1 to Au(SMe2)Cl, AgCl and CuCl, respectively. Alternatively, following the seminal discovery by Lin et al 28 on the ability of Ag(I)-NHC complexes to transfer Ag-bound NHC ligands to another metal, both the silver 10 25 and even the copper complexes 13 29 can undergo a transmetallation to give the desired CAACcoinage metal complexes.…”
Section: Synthesis Of (Caac)mcl (M = Cu Ag Au) Complexesmentioning
confidence: 99%